Optimalisasi Layanan Kesehatan Mental Melalui Intervensi Konseling Individu Di Fasilitas Kesehatan Primer - Endah Fajri Arianti; Dhian Riskiana Putri; Azzahra Anggun Salsabila (CV. SINAR HOWUHOWU, 2026)
The Surakarta City Government, through its counseling psychologist program at community health centers (Puskesmas), provides residents with easier access to quality mental health support. In line with this initiative, this community service activity aims to optimize the service by providing intensive individual counseling sessions once a month. Based on field observations, various psychosocial issues affecting the well-being of residents across all age groups—from children and adolescents to adults and the elderly—were identified. These issues range from anxiety disorders and family conflicts impacting household stability to educational challenges, school bullying, and loneliness experienced by the elderly. To address these conditions, this counseling service provides a safe and private space for residents to professionally share their mental burdens and current challenges. Furthermore, the psychologist offers practical advice on emotional management to help residents regain their spirit, mental resilience, and more harmonious family relationships. The results demonstrate that despite the limited duration, the presence of psychological services at the Puskesmas is highly effective in helping residents feel relieved and empowered. Consequently, this program represents a significant step toward supporting community well-being, strengthening family resilience, and ensuring the educational success of the younger generation.